2011
DOI: 10.1253/circj.cj-11-0033
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Distensibility and E/e' for Estimating Left Ventricular Filling Pressure in Patients With Stable Angina - A Comparative Echocardiography and Catheterization Study -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp iastolic dysfunction has a significant impact on prognosis in a wide range of cardiac disorders. 1 Noninvasive methods of estimating left ventricular filling pressure (LVFP) are often helpful for diagnosing and treating diastolic heart failure. Some echocardiographic parameters associated with left ventricular (LV) diastolic function, such as mitral inflow velocities, deceleration time, and pulmonary venous flow v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
7
32
1
1
Order By: Relevance
“…Regarding the prognostic effect of LA expansion index described in prior studies [16][17][18][19][20] and the close correlation between LA expansion index and AF progression (Figure 1), it may be conjectured that structural rather than electrical remodeling of the atria is involved in AF progression. Underlying disease might cause chronic stretch and atrial dilation, which seem to be important stimuli for chronic atrial structural remodeling.…”
Section: La Expansion Index and Persistence Of Afmentioning
confidence: 82%
See 1 more Smart Citation
“…Regarding the prognostic effect of LA expansion index described in prior studies [16][17][18][19][20] and the close correlation between LA expansion index and AF progression (Figure 1), it may be conjectured that structural rather than electrical remodeling of the atria is involved in AF progression. Underlying disease might cause chronic stretch and atrial dilation, which seem to be important stimuli for chronic atrial structural remodeling.…”
Section: La Expansion Index and Persistence Of Afmentioning
confidence: 82%
“…Recent work by the authors showed that the LA expansion index, which accurately reflects instantaneous LV filling pressure (logarithmic correlation) in many disease entities, is useful for predicting AF after coronary artery bypass graft surgery. [16][17][18][19][20] Because the LA expansion index mirrors LV filling pressure, we hypothesized that the LA expansion index predicts long-term events not only in patients with heart disease, but also in relatively low-risk subjects such as consecutive patients visiting cardiovascular clinics for dyspnea.…”
mentioning
confidence: 99%
“…2D speckle-tracking echocardiography has been used to assess E'sr, and it also has been reported to be useful in assessing LV diastolic function [47]. The original purpose of E' was to evaluate regional diastolic function, and thus it is limited with regards to assessing global diastolic function with regional functional abnormalities [48]. Moreover, the inherent limitations of Dopplerbased assessments including the potential for significant errors in angle dependency with angulations > 20° may also limit the use of E' in assessing early diastolic function.…”
Section: ) Association Between Gls and CV Outcomesmentioning
confidence: 99%
“…Therefore, it is difficult to know whether the lack of correlation is due to the characteristics of our patient population, or an insensitivity of EDP to identify early phase diastolic abnormalities. This is supported by multiple studies that have had mixed results when investigating the correlation of early diastolic echocardiographic measures to EDP [20, 25, 26]. …”
Section: Discussionmentioning
confidence: 68%